A Fractional-Order Sequential Hybrid System with an Application to a Biological System. (23rd July 2021) - Khan, Hasib; Alshehri, Hashim M.; Khan, Zareen A.
Abstract : With the help of Banach's fixed-point approach and the Leray–Schauder alternative theorem, we produced existence results for a general class of fractional differential equations in this paper. The proposed problem is more comprehensive and applicable to real-life situations. As an example of how our problem might be used, we have created a fractional-order COVID-19 model whose solution is guaranteed by our results. We employed a numerical approach to solve the COVID-19 model, and the results were compared for different fractional orders. Our numerical results for fractional orders follow the same pattern as the classical example of order 1, indicating that our numerical scheme is accurate.